Front Cover: Generating Discorrelated States for Quantum Information Protocols by Coherent Multimode Photon Addition (Adv. Quantum Technol. 5/2021). Issue 5 (14th May 2021) - Biagi, Nicola; Costanzo, Luca S.; Bellini, Marco; Zavatta, Alessandro
Abstract : Discorrelation is a new form of exclusive photon‐number anti‐correlation of multimode quantum light states, whereby measurements of the number of photons in different modes never return the same results. Discorrelated states can be used in quantum information protocols to distribute unique randomness between parties, such as implementing mental‐poker schemes between distant players, without the need for a trusted card dealer. In article number 2000141, Nicola Biagi, Alessandro Zavatta and co‐workers present the first experimental generation of discorrelated light states, obtained by coherently sharing a single photon (pictorially represented by the red sphere in the foreground) between two weak laser pulses (the two bell‐like red shapes).